Dihydropyridine Lactam Analogs Targeting BET Bromodomains. (21st December 2021) - Jiang, Jiewei; Sigua, Logan H.; Chan, Alice; Kalra, Prakriti; Pomerantz, William C.K.; Schönbrunn, Ernst; Qi, Jun; Georg, Gunda I.
Abstract: Inhibitors of Bromodomain and Extra Terminal (BET) proteins are investigated for various therapeutic indications, but selectivity for BRD2, BRD3, BRD4, BRDT and their respective tandem bromodomains BD1 and BD2 remains suboptimal. Here we report selectivity‐focused structural modifications of previously reported dihydropyridine lactam 6 by changing linker length and linker type of the lactam side chain in efforts to engage the unique arginine 54 (R54) residue in BRDT‐BD1 to achieve BRDT‐selective affinity. We found that the analogs were highly selective for BET bromodomains, and generally more selective for the first (BD1) and second (BD2) bromodomains of BRD4 rather than for those of BRDT. Based on AlphaScreen and BromoScan results and on crystallographic data for analog 10 j, we concluded that the lack of selectivity for BRDT is most likely due to the high flexibility of the protein and the unfavorable trajectory of the lactam side chain that do not allow interaction with R54. A 15‐fold preference for BD2 over BD1 in BRDT was observed for analogs 10 h and 10 m, which was supported by protein‐based 19 F NMR experiments with a BRDT tandem bromodomain protein construct. Abstract : Selectivity you can BET on : Analogs of previously reported lactam 6 with different linker lengths and linker types were found to be highly selective for BET bromodomains, and generally more selective for the first (BD1) and second (BD2) bromodomains of BRD4 rather than for those of BRDT.